Urgent Measures for the Containment of the Coronavirus (Covid-19) Epidemic in the Neurorehabilitation/Rehabilitation Departments in the Phase of Maximum Expansion of the Epidemic - Bartolo, Michelangelo; Intiso, Domenico; Lentino, Carmelo; Sandrini, Giorgio; Paolucci, Stefano; Zampolini, Mauro; , The Board of the Italian Society of Neurological Rehabilitation (SIRN) (Frontiers in Neurology, 2020)
COVID-19 has rapidly become a pandemic emergency, distressing health systems in each affected country. COVID-19 determines the need for healthcare in a large number of people in an extremely short time and, like a tsunami wave, overruns emergency, infectious diseases and pneumology departments as well as intensive care units, choking healthcare services. Rehabilitation services are also affected by this epidemic which forces radical changes both in the organization and in the operating methods. In the absence of reference literature on this issue, this report aims to provide a background documentation to support physicians and healthcare personnel involved in neurorehabilitation and rehabilitation care.